An asymptotic expansion for perturbations in the displacement field due to the presence of thin interfaces. Issue 6 (26th April 2018) - Lagha, Jihene; Zribi, Habib
Abstract : We rigorously derive an asymptotic expansion for two-dimensional displacement field associated with thin elastic inclusion having no uniform thickness. Our approach is based on layer potential techniques through integral representation formulas of the fields. We extend these techniques to determine a relationship between traction–displacement measurements and the shape of the thin inclusion.